Robotic Versus Open Pancreatoduodenectomy With Vein Resection and Reconstruction: A Propensity Score-Matched Analysis - Niccolò Napoli, MD, PhD, FEBS; Emanuele Federico Kauffmann, MD, PhD, FEBS; Michael Ginesini, MD; Armando Di Dato, MD; Virginia Viti, MD; Cesare Gianfaldoni, MD; Lucrezia Lami, MD; Carla Cappelli, MD; Maria Isabella Rotondo, MD; Daniela Campani, MD; Gabriella Amorese, MD; Caterina Vivaldi, MD; et al. (Annals of Surgery Open)
Objective:. This study aimed to compare robotic pancreatoduodenectomy with vein resection (PD-VR) based on the incidence of severe postoperative complications (SPC). Background:. Robotic pancreatoduodenectomy has been gaining momentum in recent years. Vein resection is frequently required in this operation, but no study has compared robotic and open PD-VR using a matched analysis. Methods:. This was an intention-to-treat study designed to demonstrate the noninferiority of robotic to open PD-VR (2011–2021) based on SPC. To achieve a power of 80% (noninferiority margin:10%; α error: 0.05; ß error: 0.20), a 1:1 propensity score-matched analysis required 35 pairs. Results:. Of the 151 patients with PD-VR (open = 115, robotic = 36), 35 procedures per group were compared. Elective conversion to open surgery was required in 1 patient with robotic PD-VR (2.9%). One patient in both groups experienced partial vein thrombosis. SPC occurred in 7 (20.0%) and 6 patients (17.1%) in the robotic and open PD-VR groups, respectively (P = 0.759; OR: 1.21 [0.36–4.04]). Three patients died after robotic PD-VR (8.6%) and none died after open PD-VR (P = 0.239). Robotic PD-VR was associated with longer operative time (611.1 ± 13.9 minutes vs 529.0 ± 13.0 minutes; P < 0.0001), more type 2 vein resection (28.6% vs 5.7%; P = 0.0234) and less type 3 vein resection (31.4% vs 71.4%; P = 0.0008), longer vein occlusion time (30 [25.3–78.3] minutes vs 15 [8–19.5] minutes; P = 0.0098), less blood loss (450 [200–750] mL vs 733 [500–1070.3] mL; P = 0.0075), and fewer blood transfusions (intraoperative: 14.3% vs 48.6%; P = 0.0041) (perioperative: 14.3% vs 60.0%; P = 0.0001). Conclusions:. In this study, robotic PD-VR was noninferior to open PD-VR for SPC. Robotic and open PD-VR need to be compared in randomized controlled trials.